Family history: an opportunity for early interventions and improved control of hypertension, obesity and diabetes - van der Sande Marianne A.B; Walraven Gijs E.L; Milligan Paul J.M; Banya Winston A.S; Ceesay Sana M.; Nyan Ousman A.; McAdam Keith P.W.J (The World Health Organization, 2001)
OBJECTIVE: To examine whether a family history of high-risk groups for major noncommunicable diseases (NCDs) was a significant risk factor for these conditions among family members in a study population in the Gambia, where strong community and family coherence are important determinants that have to be taken into consideration in promoting lifestyle changes. METHODS: We questioned 5389 adults as to any first-degree family history of major noncommunicable diseases (hypertension, obesity, diabetes and stroke), and measured their blood pressure (BP) and body mass index (BMI). Total blood cholesterol, triglyceride, uric acid, and creatinine concentrations were measured in a stratified subsample, as well as blood glucose (2 hours after ingesting 75 g glucose) in persons aged 35 years. FINDINGS: A significant number of subjects reported a family history of hypertension (8.0%), obesity (5.4%), diabetes (3.3%) and stroke (1.4%), with 14.6% of participants reporting any of these NCDs. Subjects with a family history of hypertension had a higher diastolic BP and BMI, higher cholesterol and uric acid concentrations, and an increased risk of obesity. Those with a family history of obesity had a higher BMI and were at increased risk of obesity. Individuals with a family history of diabetes had a higher BMI and higher concentrations of glucose, cholesterol, triglycerides and uric acid, and their risk of obesity and diabetes was increased. Subjects with a family history of stroke had a higher BMI, as well as higher cholesterol, triglyceride and uric acid concentrations. CONCLUSION: A family history of hypertension, obesity, diabetes, or stroke was a significant risk factor for obesity and hyperlipidaemia. With increase of age, more pathological manifestations can develop in this high-risk group. Health professionals should therefore utilize every opportunity to include direct family members in health education.